Analgesic Mechanism of Sinomenine against Chronic Pain - Wei Jiang; Weiming Fan; Tianle Gao; Tao Li; Zhenming Yin; Huihui Guo; Lulu Wang; Yanxing Han; Jian-Dong Jiang (Pain Research and Management)
Purified from the roots of the plant Sinomenium acutum, sinomenine is traditionally used in China and Japan for treating rheumatism and arthritis. Previously, we have demonstrated that sinomenine possessed a broad analgesic spectrum in various chronic pain animal models and repeated administration of sinomenine did not generate tolerance. In this review article, we discussed sinomenine’s analgesic mechanism with focus on its role on immune regulation and neuroimmune interaction. Sinomenine has distinct immunoregulative properties, in which glutamate, adenosine triphosphate, nitric oxide, and proinflammatory cytokines are thought to be involved. Sinomenine may alter the unbalanced neuroimmune interaction and inhibit neuroinflammation, oxidative stress, and central sensitization in chronic pain states. In conclusion, sinomenine has promising potential for chronic pain management in different clinical settings.